2016
DOI: 10.1002/acn3.339
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tau and amyloid burden on glucose metabolism in Alzheimer's disease

Abstract: In a multimodal PET imaging approach, we determined the differential contribution of neurofibrillary tangles (measured with [18F]AV‐1451) and beta‐amyloid burden (measured with [11C]PiB) on degree of neurodegeneration (i.e., glucose metabolism measured with [18F]FDG‐PET) in patients with Alzheimer's disease. Across brain regions, we observed an interactive effect of beta‐amyloid burden and tau deposition on glucose metabolism which was most pronounced in the parietal lobe. Elevated beta‐amyloid burden was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
87
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 21 publications
12
87
1
4
Order By: Relevance
“…14,44 Global cognition (measured with MMSE) declined significantly in patients with AD; this decline correlated with decreased [ 18 F]THK5317 retention (negatively); the correlations with episodic memory, however, did not survive correction for multiple comparisons and can be considered preliminary due to the small number of patients completing the episodic memory testing. The current data are in line with earlier cross-sectional findings 45 and support the notion that while tau deposition in the temporal cortex may be related to the earliest memory impairment, global cognitive changes are more closely related with hypometabolism in the relevant areas than with measures of tau propagation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,44 Global cognition (measured with MMSE) declined significantly in patients with AD; this decline correlated with decreased [ 18 F]THK5317 retention (negatively); the correlations with episodic memory, however, did not survive correction for multiple comparisons and can be considered preliminary due to the small number of patients completing the episodic memory testing. The current data are in line with earlier cross-sectional findings 45 and support the notion that while tau deposition in the temporal cortex may be related to the earliest memory impairment, global cognitive changes are more closely related with hypometabolism in the relevant areas than with measures of tau propagation.…”
Section: Discussionmentioning
confidence: 99%
“…12 Cross-sectionally, high load of tau pathology, as measured with THK5317 PET, was associated with hypometabolism in restricted brain regions, 12 while more extensive associations were reported in patients with substantially greater cognitive impairment, as measured with another tau tracer. [13][14][15] Studies with a longitudinal, multimodal design will shed light on the spreading of tau pathology in AD, and allow investigating whether the temporal trajectories of tau aggregation and hypometabolism are closely associated, or whether this association becomes closer with disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Recent imaging studies have extended prior observations first suggested by histological studies (Braak and Braak, 1991), documenting that this region typically accumulates near the lowest level of amyloid plaques throughout the cortex (e.g, (Altmann et al, 2015), yet by most indicators experiences the earliest and clearest evidence of neurotoxicity (Altmann et al, 2015; Khan et al, 2014). In fact some studies suggest that there might be an inverse relationship between levels of amyloid plaques and indicators of neurotoxicity (Altmann et al, 2015; Bischof et al, 2016). While the medial temporal lobe has low extracellular amyloid deposition, studies indicate that its neurons accumulate intracellular amyloid (Cataldo et al, 2004; Gouras et al, 2000) providing a better anatomical match to sites of dysfunction, and supporting our assumption that intracellular amyloid acts as a primary neurotoxin.…”
Section: Theraputic Implicationsmentioning
confidence: 99%
“…While the association between increased oxidative stress and increasing bioenergetic dysfunction, as evidenced by increasing glucose hypometabolism, increased lactate and pyruvate and the development of increasing synaptic dysfunction seen in preclinical AD and APOE ε4 carriers, is not associated with Aβ accumulation [257] (reviewed by [258]), recent research suggests that this might not be the case for tau deposition although findings are mixed [259][260][261]. For example, Bischof and others and Kang et al reported a positive correlation between tau deposition and glucose hypometabolism in cross-sectional studies [259,261].…”
Section: Oxidative Stress and The Development Of Synaptic Dysfunctionmentioning
confidence: 99%